Enjoying death among gamers, viewers, and users: A network visualization of Dark Souls 3's trends on Twitch.tv and Steam platforms. (July 2018) - Gandolfi, Enrico
In current Game Research, gaming service platforms such as PlayStation Network, Steam, and Twitch.tv represent a still poorly investigated topic. Despite the millions of monthly viewers and members, little efforts have been done to shed light on their dynamics and trends. This article aims to address such a lack by presenting the findings of an empirical inquiry guided by the key concepts of "platform" and "actor–network theory" with the support of a novel network visualization technique. Specifically, the role-playing game Dark Souls 3 –related activity on Steam and Twitch.tv was collected for the first 20 days from the release (12 April–1 May 2016). Targeted data concerned several variables among which: most viewed streamers, streaming types, debating topics and reviews' highlights on Steam (etc.) through screenshots, user-generated content, and text gathering. Data were processed and then visualized with the network-oriented software Gephi for uncovering associations and patterns in the targeted online environments. The action game The Division worked as an exploratory case study and counter-example for stressing the proposal. Although with some limitations, the visualization strategy adopted (four networks for each platform) proved to be effective in framing and communicating the results in a straightforward way. Finally, findings enlightened a phenomenon (i.e. gaming service platforms), that is, getting increasingly central in digital entertainment, and might inform further investigations with alternative designs and focuses.